Competitive Advantage Provided by Bacterial Motility in the Formation of Nodules by Rhizobium meliloti - Ames, Peter (1981)
The effect of motility on the competitive success of Rhizobium meliloti in nodule production was investigated. A motile strain formed more nodules than expected when mixed at various unfavorable ratios with either flagellated or nonflagellated nonmotile derivatives. We conclude that motility confers a selective advantage on rhizobia when competing with nonmotile strains.